Idiopathic pure red cell aplasia: A case series from India - Mahajan, Manoj U; Goel, Sunil; Patel, Harsh; Aasdhir, Aseem; Mehta, Urvansh; Gupta, Kavita; Sujanani, Shashi; Vishnoi, Jagdish; Patira, Nilesh; Kalu Ram Sharma (Asian Journal of Medical Sciences, 2023)
Pure red cell aplasia (PRCA) is a rare hematologic disorder characterized by normocytic normochromic anemia with reticulocytopenia and depleted erythroid precursors. It is reported mainly from western countries. We report our experience in two patients of PRCA from India, the clinical characteristics, differential diagnosis, and their management. Our patients showed improvements following treatment with corticosteroids, blood transfusion, and/or rituximab.